Cognitive dysfunction among patients referred for transcatheter aortic valve implantation: results of the Montreal Cognitive Assessment and clinical impact at 6 months. (14th October 2021) - Monnin, C; Besutti, M; Ecarnot, F; Guillon, B; Chatot, M; Chopard, R; Yahia, M; Meneveau, N; Schiele, F
Abstract: Background: Detection of Cognitive Dysfunction (CD) is not routinely performed among patients undergoing Transcatheter Aortic Valve Implantation (TAVI). We sought to determine whether CD has an impact on the clinical course of these patients, during hospitalization at the time of TAVI and up to 6 months afterwards. Methods: The MoCA was performed before TAVI by an experienced operator in an unselected population of patients referred for TAVI. CD was defined according to the MoCA score: No CD if score ≥26, mild CD if score 18–25, moderate if 10–17 and severe if <10. Multivariate Cox logistic regression analysis was used to determine the impact of CD on procedural success of TAVI, length of stay, 6 month survival, re-admission, and change in clinical status (changes in NYHA class and/or functional status). Results: MoCA was performed in 83 consecutive patients. TAVI was performed using femoral access and local anesthesia in all patients. There were no procedural deaths, and 2 deaths at 6 months. The median age was 85 years, and median Euroscore I was 11.62. The median MOCA score was 22, CD was excluded in 17 (20%), mild in 50 (60%), moderate in 15 (18%) and severe in one patient. No difference was observed in rate of procedural success, 6 month mortality, re-admission, degree of dyspnea by NYHA between the different cognitive groups. Length of stay after the TAVI procedure was lower in patients without CD, compared to those with CD at any level: 3±1 days versus 4.3±1 days, p=0.045, and p=0.02 by multivariate analysis (figure). Conclusion: Among patients referred for TAVI, mild or moderate CD was observed in 80% of patients. Patients without CD had a shorter length of stay at the time of TAVI, but CD was not associated with worse prognosis or clinical status at 6 months. Funding Acknowledgement: Type of funding sources: None.